Effect of seed rates and fertilizer levels on the yield and economics of potato (Solanum tuberosum) under north-eastern hill conditions - SINGH, KAMLA (The Indian Journal of Agricultural Sciences, 2013)
The experiment was conducted for 3 consecutive years during 1992-94 at Upper Shillong in summer season (March-July) to find out the suitable agronomic practices relating to seed and fertilizer levels to get good tuber yield. Significant increase in tuber yield was obtained up to 100, 120, 50 NPK fertilizer level. Any further increase in fertilizer level resulted only in 5.2% higher yield. Every 500 kg increase in seed rate up to 3 tonnes/ha gave significant increase in tuber yield. Fertilizer level had ’significant impact on the production of large (> 80 g) and medium (20-80 g) size tuberS, whereas seed rate had’ an impact only on the production of medium size tubers. The highest yield was obtained when both inputs applied at higher levels with the tuber prodUction ratio of 25, 58, 17 of large, medium and small size tubers respectively. But the highest net return was obtained when 2.5 tonnes seed/ha supplemented with medium (l00: 120: 60 kg NPK) fertilizer level.